Plasma β-Amyloid Levels Associated With Structural Integrity Based on Diffusion Tensor Imaging in Subjective Cognitive Decline: The SILCODE Study - Wang, Xiaoni; Zhao, Mingyan; Lin, Li; Han, Ying (Frontiers in Aging Neuroscience, 2021)
Background: Accumulating evidence has demonstrated that plasma β-amyloid (Aβ) levels are useful biomarkers to reflect brain amyloidosis and gray matter structure, but little is known about their correlation with subclinical white matter integrity in individuals at risk for Alzheimer’s disease (AD). Here, we investigated white matter microstructural changes between subjects with low and high Aβ levels in individuals with subjective cognitive decline (SCD). Methods: This study included 142 cognitively normal individuals with SCD who underwent a battery of neuropsychological tests, plasma Aβ measurements and diffusion tensor imaging (DTI) from the Sino Longitudinal Study on Cognitive Decline (SILCODE). Using tract-based spatial statistics (TBSS), we compared fractional anisotropy (FA) and mean diffusivity (MD) in white matter between subjects with low (N=71) and high (N=71) plasma Aβ levels (cut-off: 761.45 pg/mL for Aβ40 and 10.74 pg/mL for Aβ42). Results: We observed significantly decreased FA and increased MD in the high Aβ40 group compared to the low Aβ40 group in various areas, including the body, genu, and splenium of the corpus callosum, superior longitudinal fasciculus, corona radiata, thalamic radiation, external and internal capsules, inferior fronto-occipital fasciculus, and sagittal stratum (p  <  0.05, familywise error corrected). Average FA values were associated with poor performance on executive and memory assessment. No significant differences were found in either MD or FA between the low and high Aβ42 groups. Conclusion: Our results suggest that a correlation exists between white matter integrity and plasma Aβ40 levels in individuals with SCD.